PENGELOLAAN NORMA-NORMA KELOMPOK DALAM MENCAPAI TUJUAN KELEMBAGAAN DI PONDOK PESANTREN DARUSSALAM BANGUNSARI PONOROGO - Roy Maulana Iskhaq; Siti Nurjanah (Jurnal Studi Pesantren, 2025)
An educational institution is an institution that is specifically established to facilitate the teaching and learning process. Each educational institution has its own goals in developing education, which are contained in the vision, mission and objectives of an institution. To achieve this goal, rules or norms are needed. This research aims to provide knowledge about the management of group norms in achieving institutional goals in madrasas/schools. The research method used is qualitative descriptive with the type of field research. A norm is a benchmark or tool to measure a set of perspectives and human activities. Group norms are rules or guidelines of behavior that are mutually agreed upon by group members to regulate their interactions and activities. In the context of education, group norms are essential to create a conducive learning environment and achieve institutional goals. Some of the norms applied in educational institutions are religious norms, social norms, and academic norms.